REVIEW: ACTIVITY OF DIOSGENIN COMPOUND AS ATHEROSCLEROSIS THERAPY - Rusi Rismawanti; Siti Saidah (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Atherosclerosis is a disease that causes inhibition of the stability of the cardiovascular system in the body. Cardiovascular disease remains at the top of the list of diseases that cause death. Therefore, cardiovascular disease therapy, including atherosclerosis, still needs to be developed to reduce the mortality rate associated with this disease. Several studies have shown that diosgenin compounds can be used as a therapy for atherosclerosis. The purpose of this study was to determine whether diosgenin compounds and their derivatives can be used for atherosclerosis therapy with various mechanisms of action related to the development of atherosclerosis. This article review was conducted using the article search method on Google Scholar, Pubmed, and Science Direct with various keywords. The results obtained are diosgenin and several diosgenin-derived compounds that can be used as therapies for atherosclerosis with several responses obtained from experiments using rats. Keywords: diosgenin; atherosclerosis; diosgenin derivatives